Formulation and Evaluation of Natural Liposomal Gel for Breast Cancer - Thakar, B.; Agarwal, A.; Rawal, R. M. (Journal of Scientific Research, 2022)
As per world health organization (WHO) report in 2020 about 2.3 million were diagnosed globally with breast cancer and around 6.85 lacs death occurs globally due to breast cancer. In such case usage of natural anticancer remedies can provide beneficial results, but unfortunately natural drugs are not being practically useful due to trifling bioavailability and unempirical data of effectiveness. In current study, liposomal gels were formulated by using liposomes entrapped with natural compound like seasamine, aloe-emodin, gallic acid, catechin, butein, 6-gingerol and curcumin as active drugs. Liposomal gels were formulated using carbopol (1.5 % w/w) with variable concentration of propylene glycol, in another formulation mixture 1 % w/w HPMC, 1 % w/w microcrystalline cellulose and 3 % w/w sodium alginate were also used. From characterization results of all of the above formulations, formulation with 1.5 % w/w carbopol and 5 % w/w propylene glycol has shown significant release of active drugs. In addition to this penetration effect of propylene glycol was also accessed for topical liposome gel formulation; the data reveals that propylene glycol has no significant penetration boosting impact with liposomal gel formulation.